Real time inverse solution of the composites cure heat transfer problem under uncertainty - Dataset - Skordos, Alexandros A.; Tifkitsis, Konstantinos (Cranfield University, 2019)
- panel_glass.f : subroutines representing material properties and boundary conditions. - panel_glass_3.3mm.dat: Marc input corresponding to the Cure model of this paper. - Process monitoring results.xlsx: Experimental data acquired by thermocouples. - surrogate model validation.xlsx: Response surfaces of surrogate and FE model. - MCMC results: Statistical properties estimation of unknown parameters with inversion procedure. - Real time probability estimation: Minimum final degree of Cure and Minimum glass transition temperature probability estimation during manufacturing process.
Keywords: 'Inversion procedure'; 'cure process'; 'heat transfer problem'; 'Kriging'; 'Aerospace Materials'; 'Aerospace Engineering'